Experimental study on seismic behaviour of an innovative composite shear wall. (September 2018) - Huang, Shao-Teng; Huang, Yan-Sheng; He, An; Tang, Xu-Lin; Chen, Qing-Jun; Liu, Xinpei; Cai, Jian
Abstract: To improve the strength and ductility of the core walls in high-rise buildings which would be subjected to combined high axial compressive force and bending moment during the earthquake, an innovative concrete filled double-skin steel-plate composite (CFDSC) wall is proposed. The CFDSC wall is composed of the concrete filled double-skin steel-plate wall body with transverse stiffeners, vertical diaphragms and distributed batten plates welding on the internal surface of the double steel plates, and the concrete filled steel tube (CFST) columns including a pair of CFST columns positioned at the end of the cross section as boundary elements and an additional one located in the central section of the wall. Five CFDSC wall specimens were tested under constant axial compressive force and lateral reversed cyclic loading to investigate the seismic behaviour of the wall considering the effect of axial force ratio and shear span ratio. The favourable seismic performance of the CFDSC walls was demonstrated in the test. No serious pinching effect was observed on the hysteresis curves of all the specimens. The drift ratios corresponding to the ultimate stage were recorded as being in the range from 1/67 to 1/30 and the ductility coefficients were varied from 4.50 to 8.22. The experimental results manifest that the CFDSC walls have great energy dissipation capacity. Formulae for calculating the lateral load-carrying capacity of the CFDSC wall, taking the confinement effects from steel plates into account, were proposed. The results calculated by the proposed method show good agreement with the experimental results. Highlights: An innovative concrete filled double-skin steel-plate composite wall (CFDSC) is proposed. Cyclic tests on CFDSC wall specimens are presented. Formulae for calculating the lateral resistance of the CFDSC wall are suggested.